KEBIJAKAN INDONESIA DALAM MENGHADAPI PERKEMBANGAN SOCIAL COMMERCE DI INDONESIA (STUDI KASUS: TIKTOK SHOP) - Arjuna, Reza Fernanda; Fuadi, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
This study examines the Indonesian government's response to the rise of social commerce specifically on the TikTok Shop platform. This issue is important because combining social media with online shopping creates unfair competition and threatens small local businesses. There are three main problems including very cheap imported products, predatory pricing practices and the large-scale collection of user data as well as the danger to local sellers. Strong public pressure forced the government to act quickly to prevent further market damage caused by the dominance of foreign companies. The research uses a qualitative method by gathering information from various sources such as books and journals along with official documents and related news articles. The analysis applies the ideas of Mercantilism and Protectionism to understand the reasons behind the restrictions on TikTok Shop operations in Indonesia. The results show that the government clearly defines social commerce as a social media platform that can only promote products without having a direct checkout feature. Companies must have a separate license for trading to ensure that social media activities are not mixed with buying and selling. This new rule successfully deals with unfair pricing and prevents the misuse of personal data while stopping one app from controlling the entire market. The temporary shutdown forced TikTok to follow the law until they finally partnered with Tokopedia to handle their transaction system. Keywords: : Social Commerce, TikTok Shop, Protectionism, MSMEs